Optical absorption and fluorescent behaviour of titanium ions in silicate glasses - Kumar M.; Uniyal A.; Chauhan A.P.S.; Singh S.P. (My University, 2025)
Titanium in normal melting conditions in air atmosphere present as Ti4+ ion in basic silicate glasses exhibited an ultra-violet cut-off in silicate glasses, viz. soda-magnesia-silica, soda-magnesia-lime-silica and soda-lime-silica glasses. This indicates that Ti4+ ion can be a good replacement for Ce4+ ion in producing UV-absorbing silica glasses for commercial applications. The wavelength maxima at which the infinite absorption takes place in glasses was found to be around 310 nm against Ti-free blank glass in UV-region. The mechanism of electronic transition from O2- ligands to Ti4+ ion was suggested as L → M charge transfer. The low energy tails of the ultra-violet cut-off were found to obey Urbach's rule in the optical range 360-500 nm. The fluorescence spectra of these glasses were also studied and based on the radiative fluorescent properties it was suggested that the soda-lime-silica glass containing Ti4+ ion with greater emission cross-section would emit a better fluorescence than the corresponding soda-magnesia-lime-silica and soda-magnesia-silica glasses. The shift of emission wavelengths maxima towards longer wavelength in titania introduced silicate glasses was observed on replacement of MgO by CaO which may be attributed due to an increase in basicity of the glass system.